Clinical phenotype in infants with negative Zika virus immunoglobulin M testing born to mothers with confirmed Zika virus infection during pregnancy. Issue 17 (30th July 2021) - Godfred‐Cato, Shana; Newton, Suzanne; Adams, Laura; Valencia‐Prado, Miguel; Lake‐Burger, Heather; Morrison, Andrea; Jones, Abbey M.; Olson, Samantha M.; Roth, Nicole M.; Tong, Van T.; Gilboa, Suzanne M.; Meaney Delman, Dana; et al.
Abstract: Background: Recommended testing for both infants with Zika‐associated birth defects (i.e., microcephaly and selected brain or eye anomalies) and infants without birth defects whose mothers had laboratory evidence of possible Zika virus (ZIKV) infection during pregnancy includes nucleic acid amplification testing (NAAT) and immunoglobulin M (IgM) testing within days after birth. Brain and eye defects highly specific for congenital ZIKV infection have been described; sporadic reports have documented negative ZIKV testing in such infants. Methods: Infants from the U.S. Zika Pregnancy and Infant Registry and Zika Birth Defects Surveillance with Zika‐associated birth defects and maternal and infant laboratory testing for ZIKV and two congenital infections (i.e., cytomegalovirus [CMV] and toxoplasmosis) were reviewed for phenotype and laboratory results. Infants with at least one defect considered highly specific for congenital ZIKV infection were designated as having congenital Zika syndrome (CZS) clinical phenotype for this study. Results: Of 325 liveborn infants with Zika‐associated birth defects and laboratory evidence of maternal ZIKV infection, 33 (10%) had CZS clinical phenotype; 172 (53%) had ZIKV IgM testing with negative or no ZIKV NAAT. ZIKV IgM was negative in the remaining 121 infants, and for 90%, testing for CMV and toxoplasmosis was missing/incomplete. Among 11 infants testing negative for ZIKV IgM, CMV, and toxoplasmosis, 2 infants had CZS clinical phenotype. Conclusions: These data add support to previous reports of negative ZIKV IgM testing in infants with clear maternal and phenotypic evidence of congenital ZIKV infection. Follow‐up care consistent with the diagnosis is recommended regardless of infant ZIKV test results.